Making Prayer a Spiritual Strength to Eliminate Turmoil and Achieve Life's Serenity; Interpretation of the Qur'an Surah Al-Baqarah Verse 186 - viska aprillia kusuma; Siska Juliana Putri; Ali Akbar (Yayasan Adra Karima Hubbi, 2024)
Background. Life’s trials and tests often leave individuals searching for purpose and peace, particularly in times of emotional and psychological distress. This search for meaning is particularly evident among teenagers who feel lost and unsettled. As the most perfect of Allah's creations, humans are equipped with intellect and the ability to find solace in faith. Prayer becomes a key avenue through which they seek peace and stability. Purpose. The aim of this study is to understand the role of prayer in helping individuals find meaning in life, focusing on how it serves as a way to connect with Allah and attain peace. The research examines the significance of prayer as outlined in Qur'anic teachings, especially in Surah Al-Baqarah verse 186. Method. This research uses a qualitative approach, relying on library research and a descriptive method. Materials from books on Qur'anic sciences, journal articles, and Hadith are collected to support the analysis of the topic. Results. The study concludes that prayer is a vital means for humans to find peace and meaning in life. It strengthens the connection with Allah, who is always near to His servants, as explained in Surah Al-Baqarah verse 186. Prayer provides comfort, guidance, and a sense of purpose. Conclusion. Prayer is a powerful tool for finding a meaningful life, offering emotional and spiritual peace. As Allah is Qarib (near) to every servant, regular communication through prayer helps individuals navigate life’s challenges and discover inner peace.